Breakdown curves of carbon-based molecules for astrochemistry. (July 2015) - Chabot, M; Béroff, K; Gratier, P; Jallat, A; Wakelam, V; Sanchez, J P; Aguirre, N; Diaz-Tendero, S; Alcami, M; Martin, F; Hervieux, P A
Synopsis: Breakdown curves (BDC), which are energy dependent fragmentation branching ratios, constitute a kind of "identity card" of an excited molecule or cluster. We developed a method for constructing semi-empirical BDC, based on fragmentation measurements and structural known quantities of the considered species. Calculations of BDC have been performed within the statistical M3C theory. We will present a comparison of the two methods for some species and discuss application of these results to astrochemistry.